2001
DOI: 10.1016/s0272-6386(05)80004-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aging and alterations in dietary sodium intake on total nitric oxide production

Abstract: Animal studies suggest that nitric oxide (NO) deficiency is linked to salt-sensitive hypertension and that NO activity decreases during normal aging. This study investigates the impact of increasing age and manipulations in dietary salt intake on biochemical indices of the NO system in healthy humans. We measured NO 2 + NO 3 (NO X ; stable oxidation products of NO) and cyclic guanosine monophosphate (cGMP; major second messenger) in plasma and urine of 30 healthy subjects aged 22 to 77 years. Subjects were mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 36 publications
1
25
0
Order By: Relevance
“…There is clear evidence that U NO x V falls in the aging (male) rat (Reckelhoff et al, 1994;Sonaka et al, 1990;Hill et al, 1997;Erdely et al, 2003), denoting a reduction in total NO production. In man, we were unable to document a fall in U NO x V with age (Schmidt et al, 2001) although Lyons et al (1997) did report reductions in U NO x V in healthy old age. There is clearly a reduction in endothelial NO activity with age, leading to endothelial dysfunction.…”
Section: Nitric Oxidementioning
confidence: 59%
“…There is clear evidence that U NO x V falls in the aging (male) rat (Reckelhoff et al, 1994;Sonaka et al, 1990;Hill et al, 1997;Erdely et al, 2003), denoting a reduction in total NO production. In man, we were unable to document a fall in U NO x V with age (Schmidt et al, 2001) although Lyons et al (1997) did report reductions in U NO x V in healthy old age. There is clearly a reduction in endothelial NO activity with age, leading to endothelial dysfunction.…”
Section: Nitric Oxidementioning
confidence: 59%
“…SILVA [9] suggested that ageing should be seen as the erosion of generous spare capacity or loss of renal safety margins. The tubular systems becomes less capable of conserving or excreting NaCl [14]. Among the elderly, exsiccation and/or hyponatraemia becomes prevalent [15].…”
Section: Thoracic Oncology C Máthé Et Almentioning
confidence: 99%
“…Dietary calcium reduces blood pressure by stabilizing the arterial membranes, blocking its own entry into the cell, inhibiting contraction of arterial smooth muscles and by enhancing NO synthesis (Passmore et al, 1997;Das, 2001a). Conversely, high salt intake reduces NO synthesis, although this action has been disputed (Schmidt et al, 2001). High salt intake initially stimulates NO production (to maintain normotension despite increase in blood volume caused by increased salt intake) to maintain blood flow, and only when the enhanced salt intake continues for a long time, NO synthesis is decreased (possibly because of the exhaustion of the eNOS activity), which leads to the development of hypertension (Nakanishi et al, 2002).…”
Section: No and Hypertensionmentioning
confidence: 99%